Procedimentos e projeto de demolições para edificações em concreto armado - Martins, Pedro Henrique Santos (2019)
Demolition is the process of planned fragmentation of elements of construction that can be total, representing the ruin of the building, or partial, occurred in reforms and structural changes. However, it is considered as a risk activity, as it is often affected structural elements, and consequently, the static behavior of the building, and the study of the demolition project and controlled collapse is left without specific criteria. This research features a study of national and international standards, guidelines and code of practices that discuss the project and the useful techniques for demolition of reinforced concrete structures. In Brazil, the demolition is executed through empirical methods and often without technical safeguard, since the Brazilian norm that regulated the contracting and offered guidelines for the execution of demolition services was canceled. Therefore, were presented a study of the Brazilian norm canceled and standards of other countries, showing their differences and procedures, as well as the main current techniques, such as: manual, mechanical, wire rope pulling demolition, by explosives, wrecking ball, chemical demolition, thermal procedures and by hydrodemolition with pressure jet. Therefore, the different techniques are presented, the considerations for project and execution of demolitions and examples of projects applications, which is presented and discussed the planning criteria. The decision of the most appropriate method should be made by evaluating the factors of restriction, cost, availability of equipment and access, distance of neighboring buildings, the state of the structure and meteorological conditions. Thus, according to what was observed, it was concluded that a preliminary adequacy of the building to be demolished is important, to consider the most efficient and effective method in its correct dismantling and disposal of the waste generated.